Pseudo-Bartter’s syndrome in patients with cystic fibrosis: A case series and review of the literature - Vilotijević-Dautović Gordana; Stojanović Vesna (Srpski Arhiv za Celokupno Lekarstvo, 2015)
Introduction. Pseudo-Bartter syndrome (PBS) is characterized by hyponatremic, hypochloremic metabolic alkalosis that mimics Bartter syndrome but with no pathology in the renal tubules. We present five patients with cystic fibrosis (CF) and PBS. Cases Outline. Four children aged between three and five-and-one-half months with previously diagnosed CF and one aged 17 months with previously undiagnosed disease, were hospitalized during the summer season, with severe dehydration, oliguria, apathy and adynamia. Additionally, one of them had an ileostomy due to meconium ileus after birth. All children were on a diet without additional salt intake. Laboratory analysis on admission showed hyponatremia (115-133 mmol/L, mean 122.4 mmol/L), high plasma renin activity (229-500 pg/ml, mean 324 pg/ml) and metabolic alkalosis (pH 7.5-7.6, mean 7.56) in all the patients, and in four of them high blood level of aldosterone (74-560 pg/ml, mean 295.9 pg/ml), hypokalemia (2.3-2.8 mmol/L, mean 2.6 mmol/L), hypochloremia (59-71 mmol/L, mean 66 mmol/L) and low urinary sodium (5-12 mmol/L, mean 9 mmol/L). After intravenous rehydration followed by additional use of sodium and chloride in mean dosis of 1.78 mmol/kg per day, all the patients made a complete recovery. With advice for additional use of salt in the mentioned amount, the patients were discharged from the hospital. Conclusion. PBS is one of CF complications, especially in infants and young children in situations accompanied by increased sweating and/or other causes of additional loss of sodium and chlorine. Sometimes, as was the case with one of our patients, PBS may be the initial presentation form of the disease.